1984
DOI: 10.2466/pr0.1984.55.2.619
|View full text |Cite
|
Sign up to set email alerts
|

A Multi-Vantaged Approach to Measurement of Behavioral and Affect States for Clinical and Psychobiological Research

Abstract: The development of methods based on the “multivantaged” assessment of behavioral, affect, and cognitive constructs in patients with affective disorders, is reponed. The state and outcome constructs were derived for application in clinical and psychobiological studies, particularly those aimed at testing biobehavioral hypotheses and the evaluation of the effects of drugs. The development of the constructs is based on the combining of scales from established measures which assess the patient in the interview, on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

1986
1986
2005
2005

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 68 publications
(37 citation statements)
references
References 19 publications
0
37
0
Order By: Relevance
“…Other measures of the components of depression, for example, psychomotor performance, derived from our earlier work, are described below. These have been described previously (Katz et al, 1982(Katz et al, , 1984(Katz et al, , 1989.…”
Section: Measurement Of Behavioral Components and Severity Of The Depmentioning
confidence: 99%
See 2 more Smart Citations
“…Other measures of the components of depression, for example, psychomotor performance, derived from our earlier work, are described below. These have been described previously (Katz et al, 1982(Katz et al, , 1984(Katz et al, , 1989.…”
Section: Measurement Of Behavioral Components and Severity Of The Depmentioning
confidence: 99%
“…In this multivantaged approach (Katz et al, 1984), doctor ratings included the Ham-D, CGI, Schedule for Affective Disorders, and SchizophreniaChange Version (SADS-C, Endicott and Spitzer, 1978), Global Assessment Scale (GAS, Endicott et al, 1976), Video Interview Behavioral Evaluation Scales (VIBES) (Katz and Itil, 1974); nurse ratings: the Affective Disorder Rating Scale (ADRS) (Murphy et al, 1980), NIMH Mood Scale (Raskin et al, 1969), Global Ward Behavior Scale (Raskin et al, 1969); patient self-reports included the Symptoms Checklist (SCL-90; Derogatis et al, 1974); NIMH Mood Scale (Raskin et al, 1969); and the Buss-Durkee Hostility Inventory (Buss and Durkee, 1957). Other measures of the components of depression, for example, psychomotor performance, derived from our earlier work, are described below.…”
Section: Measurement Of Behavioral Components and Severity Of The Depmentioning
confidence: 99%
See 1 more Smart Citation
“…Discovering how these methods can be combined to meet the objective of devising primary outcome indices and measures of the major components requires psychometric analysis of large sample data in which the methods have been applied alongside the conventional severity rating scales. Examples of systems based on combining several diverse test procedures are found in Raskin et al (1967), and in Katz et al (1984). The values of the componential approach in meeting current problems of evaluation are further examined in the section on measuring onset and speed of action of the new drugs.…”
Section: Conceptions Of Depression and The Mechanisms Of Drug Actionmentioning
confidence: 99%
“…Examination in the previous study (Maas et al 1980;Katz et al 1979) of the average componential prohle for a severely depressed sample of 104 patients indicated that the level of anxiety in those patients was almost as high as the level of depressed mood and that hostil ity was signiftcantly higher than in healthy controls (Katz et al 1984).…”
Section: On the Structure Of Depressionmentioning
confidence: 99%